Influence of fibroids on cell‐free DNA screening accuracy. (5th January 2022) - Scott, F.; Menezes, M.; Smet, M. E.; Carey, K.; Hardy, T.; Fullston, T.; Rolnik, D. L.; McLennan, A.
ABSTRACT: Objective: Cell‐free DNA (cfDNA) screening assesses both maternal and placental cfDNA. Fibroids are common and release cfDNA into maternal serum. Genetic abnormality is seen in 50% of fibroids. We aimed to assess the impact of fibroids on the accuracy of genome‐wide cfDNA screening. Methods: This was a prospective cohort study of singleton pregnancies examined at one of two centers in Melbourne and Sydney, Australia, between 1 November 2019 and 31 December 2020. All cases underwent pretest ultrasound examination to confirm an ongoing pregnancy of at least 10 weeks' gestation, and, at this stage, the number and volume of any uterine fibroid were documented. Genome‐wide cfDNA screening was performed to detect all copy‐number variants (CNV) > 7 megabases. The incidence of a false‐positive result was compared between cases with and those without fibroids. Results: Over the 14‐month study period, 13 184 patients underwent cfDNA screening, of whom 1017 (7.7%) had fibroids. Fibroids were not identified in any of the 17 participants who had a false‐positive result for chromosomes 13, 18, 21, X or Y. Ninety‐five (0.7%) cases were screen‐positive for subchromosomal aberration (SA), rare autosomal trisomy (RAT) or multiple abnormalities (MA), with 10 of these cases having a fetal genetic abnormality. The incidence of a false‐positive RAT, MA or SA result was significantly higher in participants with fibroids (20/1017 (2.0%)) than in those without fibroids (64/12 167 (0.5%)). Women with fibroids were approximately six times as likely to have a false‐positive result for SA, and this was associated positively with both fibroid number and volume. Conclusions: Most women with fibroids do not have an abnormal result on genome‐wide cfDNA screening. However, CNVs due to fibroids are associated with false‐positive SA findings, although fibroids do not appear to influence cfDNA screening accuracy for the common autosomal trisomies or sex‐chromosomal abnormalities. © 2021 International Society of Ultrasound in Obstetrics and Gynecology. Abstract : Linked article: There is a comment on this article by Yang et al. Click here to view the Correspondence.